Justifiably Improved Model for Car Engine and Lighting Simulation: A Teaching Device for Automotive Servicing, National Competency Level 1 (NC 1) - Pecaso, J P; Pecaso Jr, J P (KnE Social Sciences, 2018)
Learning engine and chassis electrical system in automotive technology should conform to the manipulative requirements of the Technical Education Skills Development Authority (TESDA). National Competency (NC) in levels I, and II requires tedious trainings for automotive student-trainees in order to pass the TESDA certification body. Subsequently, the K-12 program of the Department of Education(Dep-Ed) in the country offering automotive as one of it’s course should be made acceptable and compliant to the TESDA National Competency (NC) standard as embodied in the Philippine TVET Qualifications Framework (PTQF. Infancy of the program offering require trainers, mock-ups and relative educational materials in automotive technology to facilitate and heighten automotive technology instructions specially in the implementation of the K-12 program. A need to design, develop, try-out and evaluate an environment-friendly instructional device for automotive technology using locally available materials was made and utilized with aims to enhance the manipulative skill of the trainees. The researchers opted to follow the Research and Development (R&D) process. The descriptive method was introduced through a survey questionnaire to automotive technology students, mentors of Partido State University (PSU) and selected shop owners in the locality as respondents. T-test is also applied to further validate the study. The instructional model was introduced in automotive mainly for learning automotive engine and chassis electricity, thus this study was conceptualized. Keywords: automotive technology, chassis wiring, design, engine electricity, instructional model